2021
DOI: 10.3390/molecules26051458
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Method for Stabilizing Zein Gel Particles to Salt Ion-Induced Aggregation

Abstract: The destabilization of zein gel particles by salt ions seriously limits their practical application. In this study, zein gel particles exhibiting excellent stability to salt ions were developed by grafting gum arabic with tannic acid. Gum arabic (GA) was first coated onto the surface of zein gel particles, followed by addition of tannic acid to further reinforce non-covalent cross-linking between GA and the zein gel particle surface. The stability of the gel particle dispersions was characterized by Turbiscan … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…The pH of the zein solution and the OSA-modified starch solution were adjusted to 4.0 or 9.0 with 0.1 mol/L of HCl or NaOH solution, respectively. The zein/OSA-modified starch nanoparticles were prepared using the antisolvent precipitation method [7] with some modifications. A total of 20 mL of 2% (w/v) zein aqueous ethanol solution was added drop by drop into 380 mL of OSA-modified starch solution with the same pH to fabricate zein/OSA-modified starch nanoparticles.…”
Section: Preparation Of Zein/osa-modified Starch Nanoparticlesmentioning
confidence: 99%
See 1 more Smart Citation
“…The pH of the zein solution and the OSA-modified starch solution were adjusted to 4.0 or 9.0 with 0.1 mol/L of HCl or NaOH solution, respectively. The zein/OSA-modified starch nanoparticles were prepared using the antisolvent precipitation method [7] with some modifications. A total of 20 mL of 2% (w/v) zein aqueous ethanol solution was added drop by drop into 380 mL of OSA-modified starch solution with the same pH to fabricate zein/OSA-modified starch nanoparticles.…”
Section: Preparation Of Zein/osa-modified Starch Nanoparticlesmentioning
confidence: 99%
“…It has been reported that the interactions between protein and polysaccharide significantly influence the properties of nanoparticles, such as conformational stability [6]. To improve the stability of zein nanoparticles against different pH levels, many biopolymers have been used to stabilize zein by forming complex particles [3] such as gum arabic [7], alginate oligosaccharide [2], whey protein isolate [8], and ι-carrageenan [5]. Thus, combining zein with biopolymers has proven to be an effective strategy to prevent zein nanoparticles from aggregation and precipitation over a broad pH range.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous work, we designed zein-gum arabic-TA (zein-GA-TA) composite particles with high physical stability based on the physicochemical properties of TA ( 16 ). The introduction of TA could link the protein part of GA crosslinked with the protein on the surface of the zein particles through hydrogen bonding.…”
Section: Introductionmentioning
confidence: 99%